Flood Risk and Resilience - Fu, Guangtao; Casado, Monica Rivas; Meng, Fanlin; Kalawsky, Roy; Fu, Guangtao; Casado, Monica Rivas; Meng, Fanlin; Kalawsky, Roy (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Flooding is widely recognized as a global threat, due to the extent and magnitude of damage it causes around the world each year. Reducing flood risk and improving flood resilience are two closely related aspects of flood management. This book presents the latest advances in flood risk and resilience management on the following themes: hazard and risk analysis, flood behaviour analysis, assessment frameworks and metrics and intervention strategies. It can help the reader to understand the current challenges in flood management and the development of sustainable flood management interventions to reduce the social, economic and environmental consequences from flooding.
English
Keywords: History of engineering & technology; nonstationarity; univariate model; GAMLSS; bivariate model; copulas; floodway; optimization; particle swarm optimization; HEC-RAS; flood mitigation; hydraulic modeling; flood risk perception; natural flood management; disaster mitigation; flood-prone city; questionnaire survey; flood hazard; land use; urban growth; Villahermosa; architecture modelling flood resilience; resilience engineering; system-of-systems water systems; multi-risk matrix; resilience; flood risk; multi-hazard; risk reduction; flood resilience index; flood resilience analysis; urban floods; flood risk assessment; flood inundation modelling; Artificial Intelligence; machine learning; flood; preparedness; flood resilience; blue-green infrastructure; flood risk management; sustainable; drainage systems; systems; flood control materials; intelligent warehousing; location allocation; multi-objective optimization; drone applications; deployment time; monitoring; flood modelling; evacuation; rescue; management strategy; metrics